Developing plurilinguism in slovakia: the clil method, a starting point (2004)
The paper deals with an introduction of the CLIL (Content and LanguageIntegrated Learning) - a newly invented and officially recommended method for the teaching of foreign languages in the European Union. The authors describe its general characteristics and benefits as well as give examples of its application in Slovakia, one of the new member states of the EU. Since Slovakia is not widely known in Colombia, the authors have added a description of the situation in teaching foreign languages in their country, thus providing an important context for teaching objectives and conditions of applying the CLIL. Key words: Plurilinguism, Foreign Language Teaching-Young Learners, CLILMethodology Este documento trata sobre la introducción del método (Contenido y Lenguaje integrados en el aprendizaje) CLIL – una nueva metodología diseñada y oficialmente recomendada como método de enseñanza de lenguas extranjeras en la Unión Europea. Las autoras describen las características generales del método y sus beneficios, así como ejemplos de su aplicación en Eslovenia, uno de los nuevos miembros de la UE. Debido a que Eslovenia no es muy conocida en Colombia, las autoras han incluido una descripción de la situación de la enseñanza de lenguas extranjeras en su país. De tal manera, proveen un contexto importante para los objetivos y condiciones de la enseñanza en la aplicación de esta metodología. Palabras claves: Plurilingüismo, Enseñanza-Lenguas Extranjeras- Estudiantes-Jóvenes, CLIL-Metodología